Legacy and novel perfluoroalkyl and polyfluoroalkyl substances in industrial wastewater and the receiving river water: Temporal changes in relative abundances of regulated compounds and alternatives. (1st March 2021) - Kim, Ki Yong; Ndabambi, Mlamuli; Choi, Sol; Oh, Jeong-Eun
Highlights: A PFAS emission inventory for an industrial complex in south korea was compiled. C <7 PFASs are used as alternatives to C8 PFASs by korean industries. Novel alternative PFASs were not detected in any of the industrial wastewater samples. Changes in PFAS use in the last 10 y were indicated by river water concentrations. Abstract: Concentrations of 28 novel and legacy perfluoroalkyl and polyfluoroalkyl substances (PFASs) in wastewater from 77 industrial plants in the largest industrial complex in Korea were determined. The industrial plants were of eight types (advanced electronic, battery, chemical, general electronic, glass and ceramic, metal, polymer, and textile). PFAS concentrations in river water receiving the wastewater were determined to assess the impact of wastewater from the industrial complex. Only 19 and nine target PFASs were detected in untreated industrial wastewater and river water, respectively. Novel PFASs such as F53B (6:2 chlorinated polyfluoroalkyl ether sulfonate) were not detected. The mean PFASs concentration in industrial wastewater treatment plant effluent was 5.18 µg/L. The mean total PFASs concentration was highest in advanced electronic plant effluent, second highest in general electronic plant effluent, and lowest in battery and chemical plant effluents. Perfluorohexane sulfonate was the dominant homolog, being detected in effluent from plants of all classes and contributing 96% of total discharged PFASs by mass. Perfluorooctane sulfonate (included in the Stockholm Convention) use has decreased markedly since previous studies. Perfluorooctane sulfonate has largely been replaced by PFASs with fewer than seven carbon atoms. A similar change was found for river water receiving industrial wastewater. Graphical abstract: Image, graphical abstract